2020
DOI: 10.1002/cne.24999
|View full text |Cite
|
Sign up to set email alerts
|

Brain of the African wild dog. I. Anatomy, architecture, and volumetrics

Abstract: The African wild dog is endemic to sub‐Saharan Africa and belongs to the family Canidae which includes domestic dogs and their closest relatives (i.e., wolves, coyotes, jackals, dingoes, and foxes). The African wild dog is known for its highly social behavior, co‐ordinated pack predation, and striking vocal repertoire, but little is known about its brain and whether it differs in any significant way from that of other canids. We employed gross anatomical observation, magnetic resonance imaging, and classical n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 61 publications
2
12
0
Order By: Relevance
“…Thus, the present study details our observations, based on cytoarchitecture, myeloarchitecture and several immunohistochemical stains, of the olfactory system within the brain of the African wild dog, continuing our investigation of the brain of this species (Chengetanai et al, 2020).…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…Thus, the present study details our observations, based on cytoarchitecture, myeloarchitecture and several immunohistochemical stains, of the olfactory system within the brain of the African wild dog, continuing our investigation of the brain of this species (Chengetanai et al, 2020).…”
Section: Introductionsupporting
confidence: 53%
“…Ten adult African wild dog brains were obtained from Borås Zoo, Sweden (see Chengetanai et al, 2020 for full details of animals, permits and collection and treatment of tissue). All animals were treated and used according to the guidelines of the University of the Witwatersrand Animal Ethics Committee (AESC No.…”
Section: Specimensmentioning
confidence: 99%
“…The auditory cortical territory identifiable with the range of stains used in the current study was observed to occupy the ectosylvian gyrus, bordered medially by the suprasylvian sulcus and laterally by the ectosylvian sulcus (Figure 6, also see Chengetanai, Tenley, et al, 2020a for sulcal and gyral demarcations and nomenclature in the African wild dog). With the stains used in the current study we were able to identify the primary auditory cortex (AI), the anterior auditory field (AAF), and a larger region which we termed the secondary auditory cortex (AII), although we recognize that this region is likely to be comprised of at least two smaller cortical areas, the posterior pseudosylvian field and posterior suprasylvian field (e.g., Bajo, Nodal, Bizley, Moore, & King, 2007; Bizley, Nodal, Nelken, & King, 2005).…”
Section: Resultsmentioning
confidence: 56%
“…Ten adult African wild dog brains were obtained from Borås Zoo, Sweden (see Chengetanai, Tenley, et al, 2020a for full details of animals, permits, and collection and treatment of tissue). Antemortem observations for all these animals revealed that they were in good health with no obvious neural deficits or behavioral abnormalities, and were euthanized for population management reasons (Bertelsen, 2018).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation